Notes on fine structures of Chauliops with descriptions of two new species from China (Insecta: Hemiptera: Heteroptera: Malcidae) - Gao, Cuiqing; Bu, Wenjun (Zootaxa, 2009)
The fine structures of Chauliops were studied using scanning electron microscope (SEM) techniques, and its taxonomic significance was discussed. Two new species of Chauliops Scott, Chauliops quaternaria sp. nov., from China (Yunnan province), and Chauliops conica sp. nov., from China (Shaanxi province), were described. A key to the known species of Chauliops Scott from China was given. The type specimens of the new species are deposited in the Institute of Entomology, Life Sciences College of Nankai University, Tianjin, China.